Primary Teacher Education in Trinidad And Tobago - Quamina-Aiyejina, Lynda; Mohammed, Jeniffer; Rampaul, Balchan; George, June; Kallon, Michael; Keller, Carol; Lochan, Samuel (School of Education, The University of the West Indies, St. Augustine, Trinidad and Tobago, West Indies, 1998)
A baseline study provides a historical overview of the development of the teacher Education system in Trinidad and Tobago, against the background of a description of the country’s education system. An overview of the contemporary teacher education system is also provided, as well as analysis of: 1) teacher education curricula, 2) the quality and effectiveness of teacher education, 3) teacher identities, attitudes and roles, 4) resources of teacher education 5) emerging issues.
Muster Project
A Baseline Study
Keywords: Muster Project